Pedagogical Adaptation of Arabic Language Teachers in Responding to the Implementation of the Merdeka Curriculum at Integrated Islamic Junior High Schools: Challenges and Solutions - Adibah Ulaya Putri; Sofyan Sauri; Mad 'Ali (Universitas Cokroaminoto Palopo, 2026)
This study aims to describe and analyze the pedagogical adaptation of an Arabic language teacher in implementing the Merdeka Curriculum at an Integrated Islamic Junior High School, identify the challenges encountered, and examine the strategies developed to address them. The low interest among students in Arabic, the gap in prior knowledge between graduates of Islamic elementary schools and public elementary schools, and the influence of digital culture on students' language habits are among the key issues underlying this study. Using a qualitative approach with an interpretive paradigm and a descriptive case study design, one Arabic language teacher was selected as the research subject through purposive sampling based on their direct involvement in the implementation of the Merdeka Curriculum and their active use of digital media in teaching. Data were collected through semi-structured interviews and document analysis, then analyzed using Miles and Huberman's interactive model through three stages: data reduction, data display, and conclusion drawing. The findings reveal three main results. First, pedagogical adaptation is still largely at the administrative adjustment stage, where changes are more visible in lesson plan documents than in actual classroom practice. Second, the teacher has begun shifting toward student-centered learning, differentiated instruction, and creative strategies, such as creating video content, using Quizizz, and simple Arabic language habituation in daily classroom interactions. Third, the main challenges include low student motivation, gaps in ability due to diverse educational backgrounds, and the impact of digital culture and generational differences. Teacher flexibility and reflectivity proved to be key factors in sustaining teaching quality amid these limitations. This study contributes to filling the research gap on Arabic language teachers' pedagogical adaptation in Integrated Islamic Junior High School, which integrates the national curriculum with the Islamic institutional curriculum.